KODE KEHORMATAN PRAMUKA PERSPEKTIF FILSAFAT MORAL DAN SUMBANGSIH TERHADAP PENDIDIKAN KARAKTER - Firmansyah, Mursyidul Haq (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2021)
Morality is a very hot discussion these days, Morality is an effort to guide someone’s action with common sense. Moral philosophy is a critical, systematic, and methodical science about the deeds of human beings and its relation to the good and bad. Code of scout honor sections of the code of ethics is interesting to study moral values contained in it. Type of this research is qualitative method; the formal object was moral philosophy while the material object was the code of honor of the boy scouts. The approach method that used in this research was ethics normative, and the analysis method was the philosophical interpretation. In the moral Values in the code of honor of the boy scouts is the crystallization of value-the value of life taken from the values in the life only for a while of the society. The value of moral rights and obligations, justice, honesty, responsibility and attitude of humble can become the norm which is universal so it can be a reference norm for human beings in general. In addition, these norms enrich moral values in character of education.